2023
DOI: 10.9734/ijpss/2023/v35i143043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Application of Boron and Silicon on Growth and Yield of Maize (Zea mays L.)

Abstract: This field experiment was carried out during Zaid season 2022 at experimental field of Crop Research Farm, Department of Agronomy, Naini Agricultural Institute, Sam Higginbottom University of Agriculture, Technology& Sciences, Prayagraj, Uttar Pradesh, India. The soil of experimental plot was sandy loam in texture, nearly neutral in soil reaction (pH7.3), low in organic carbon (0.48%), available nitrogen (230 kg/ha), available phosphorus (13.60 kg/ha) and available potassium (215.4 kg/ha).. Ten treatments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Foliar application of B has a positive effect on the growth and yield of maize. Treatment with B at 4 kg/ha and Panchagavya at 4% produced maximum plant height, plant dry weight, number of cobs per plant, cob yield with and without husk, and green fodder yield [34]. Another study found that foliar application of B at 0.3% resulted in significantly higher growth parameters such as plant height, plant dry weight, and crop growth rate, as well as yield attributes like number of cobs per plant, number of grains per cob, and grain yield [37].…”
Section: Different Methods Of Boron Applicationmentioning
confidence: 97%
See 3 more Smart Citations
“…Foliar application of B has a positive effect on the growth and yield of maize. Treatment with B at 4 kg/ha and Panchagavya at 4% produced maximum plant height, plant dry weight, number of cobs per plant, cob yield with and without husk, and green fodder yield [34]. Another study found that foliar application of B at 0.3% resulted in significantly higher growth parameters such as plant height, plant dry weight, and crop growth rate, as well as yield attributes like number of cobs per plant, number of grains per cob, and grain yield [37].…”
Section: Different Methods Of Boron Applicationmentioning
confidence: 97%
“…It was found that the application of 15 kg of zinc with 1.5% B as a foliar spray resulted in increased plant height, number of leaves per plant, plant dry weight, number of cobs per plant, number of grains per cob, and grain yield [10]. Another study showed that the treatment of 100 ppm B combined with 700 ppm silicon significantly increased plant height, number of leaves per plant, plant dry weight, and yield attributes in maize [34,35]. Finally, a study on sandy loam soils with different levels of B found that the non-specifically adsorbed B fraction was higher after the application of B, and the plant available form of boron included the non-specifically adsorbed fraction, which coincided with the high demand for B by maize during the vegetative phase [36].…”
Section: Different Methods Of Boron Applicationmentioning
confidence: 99%
See 2 more Smart Citations